2022
DOI: 10.3389/fnhum.2022.773593
|View full text |Cite
|
Sign up to set email alerts
|

Structural Features Predict Sexual Trauma and Interpersonal Problems in Borderline Personality Disorder but Not in Controls: A Multi-Voxel Pattern Analysis

Abstract: Child trauma plays an important role in the etiology of Bordeline Personality Disorder (BPD). Of all traumas, sexual trauma is the most common, severe and most associated with receiving a BPD diagnosis when adult. Etiologic models posit sexual abuse as a prognostic factor in BPD. Here we apply machine learning using Multiple Kernel Regression to the Magnetic Resonance Structural Images of 20 BPD and 13 healthy control (HC) to see whether their brain predicts five sources of traumas: sex abuse, emotion neglect,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

5
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 90 publications
0
12
0
Order By: Relevance
“…Images were segmented into GM and WM partitions using the segmentation procedure (Ashburner & Friston, 2005) as implemented in SPM12 (Statistical Parametric Mapping software, version 12; http://www.fil.ion.ucl.ac.uk/spm; Wellcome Department of Imaging Neuroscience, London), normalized to MNI space and spatially smoothed (full‐width at half maximum of Gaussian smoothing kernel [8, 8, 8]). Multivariate regression analysis was performed using Kernel ridge regression (KRR), a valid method enabling high predictive accuracy (Chu et al, 2011; Orsenigo & Vercellis, 2012), even in case of relatively small samples and single‐subjects (Dadomo et al, 2022; Schumacher et al, 2019). KRR is a multivariate regression method equivalent to maximum a posteriori approach to Gaussian process regression with fixed prior variance and no explicit noise term.…”
Section: Methodsmentioning
confidence: 99%
“…Images were segmented into GM and WM partitions using the segmentation procedure (Ashburner & Friston, 2005) as implemented in SPM12 (Statistical Parametric Mapping software, version 12; http://www.fil.ion.ucl.ac.uk/spm; Wellcome Department of Imaging Neuroscience, London), normalized to MNI space and spatially smoothed (full‐width at half maximum of Gaussian smoothing kernel [8, 8, 8]). Multivariate regression analysis was performed using Kernel ridge regression (KRR), a valid method enabling high predictive accuracy (Chu et al, 2011; Orsenigo & Vercellis, 2012), even in case of relatively small samples and single‐subjects (Dadomo et al, 2022; Schumacher et al, 2019). KRR is a multivariate regression method equivalent to maximum a posteriori approach to Gaussian process regression with fixed prior variance and no explicit noise term.…”
Section: Methodsmentioning
confidence: 99%
“…Prospective longitudinal research provided further evidence for the hypothesis that exposure to adverse events in childhood increased the risk of being diagnosed with BPD in adulthood [42; 43; 44; 45]. In a previous attempt to assess the impact of traumatic experiences on the brain of BPD patients, Dadomo and colleagues [46] reported evidence that a circuit including the amygdala, the Heschl area, the Caudate, the Putamen, and portions of the Cerebellum was predictive of sexual abuse. They also reported that another circuit involving temporal and cerebellar regions was predictive of interpersonal problems.…”
Section: The Present Studymentioning
confidence: 99%
“…The aim is not only to explore the neural bases of anxiety, but also to extract a neural model to predict trait anxiety. As such, this model can pave the way for the creation of a potential biomarker to predict new cases (Dadomo et al, 2022;Grecucci et al, 2022).…”
Section: Introductionmentioning
confidence: 99%